2017
DOI: 10.2174/1871520616666161019143219
|View full text |Cite
|
Sign up to set email alerts
|

Docking and QSAR Studies of Aryl-valproic Acid Derivatives to Identify Antiproliferative Agents Targeting the HDAC8

Abstract: Based on theoretical studies, compound DAVP042 was synthesized and evaluated in vitro for its antiproliferative activities on several cancer cell lines (A549-lung, MCF-7-breast, HCT116-colon and U937- lymphoid tissue) in comparison to VPA, as well as for its inhibitory activity on HDAC8 using in vitro models. DAVP042 demonstrated to have antiproliferative activity on all cancer cell lines employed, not only suggesting that this compound should be further studied, but also demonstrating that the methodology her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Nevertheless, numerous studies support the tumorigenic role of HDAC8 and confirmed that genetic ablation or pharmacological inhibition of HDAC8 reduces cell proliferation, suppresses colony formation, and induces cell cycle arrest in cancer [25,29,36,84,89,90,92,94,95]. Upregulation of apoptosis is also frequently observed when cancer cells are treated with HDAC8is [94,[96][97][98][99]. HDAC8 depletion or inhibition induces p53/p21-mediated apoptosis in HCC cells, Bcl2 modifying factor-mediated apoptosis in gastric cancer and colon cancer cells, and caspase-dependent apoptosis in T cell lymphomas [31,49,89,100].…”
Section: Cancer Cell Proliferation and Apoptosismentioning
confidence: 99%
“…Nevertheless, numerous studies support the tumorigenic role of HDAC8 and confirmed that genetic ablation or pharmacological inhibition of HDAC8 reduces cell proliferation, suppresses colony formation, and induces cell cycle arrest in cancer [25,29,36,84,89,90,92,94,95]. Upregulation of apoptosis is also frequently observed when cancer cells are treated with HDAC8is [94,[96][97][98][99]. HDAC8 depletion or inhibition induces p53/p21-mediated apoptosis in HCC cells, Bcl2 modifying factor-mediated apoptosis in gastric cancer and colon cancer cells, and caspase-dependent apoptosis in T cell lymphomas [31,49,89,100].…”
Section: Cancer Cell Proliferation and Apoptosismentioning
confidence: 99%